Corporate Governance dan Efisiensi Investasi - Jannah, Hanifah Roudhotul; Rahmawati, Isna Putri (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2020)
The purpose of this study is to examine the effect the effectiveness of the board of commisioners and audit committee on the investment efficiency. The effectiveness of the board of commisioners and audit committee is measured by the effective score based on some indicators. This study uses 209 year-observations of companies listed in Jakarta Islamic Index during 2008-2017 period. This study shows that the effectiveness of the board of commisioners has no effect on the underinvestment, while the effectiveness of the audit committee has negative effect on the underinvestment. In addition, the effectiveness of the board of commisioners has negative effect on the overinvestment while the effectiveness of the audit committee has positive effect on the overinvestment. Penelitian ini bertujuan untuk menguji pengaruh efektivitas dewan komisaris dan efektivitas komite audit terhadap efisiensi investasi. Efektivitas dewan komisaris dan efektivitas komite audit diukur dengan menggunakan skor efektivitas yang dinilai berdasarkan beberapa indikator. Sampel penelitian ini menggunakan 209 observasi dari perusahaan yang termasuk dalam Jakarta Islamic Index periode 2008-2017. Hasil penelitian menunjukkan bahwa efektivitas dewan komisaris tidak berpengaruh signifikan terhadap underinvestment, sedangkan komite audit berpengaruh negatif dan signifikan terhadap underinvestment. Selain itu, efektivitas dewan komisaris berpengaruh negatif dan signifikan terhadap overinvestment sedangkan efektivitas komite audit berpengaruh positif dan signifikan terhadap overinvestment.